Analyzing Socio-Economic Determinants of Out-Migration in 5 ASEAN Countries - Mufarihah, Ni'matim; Nihayah, Annis Nurfitriana (Forum Kerjasama Pendidikan Tinggi, 2025)
International migration has become an important phenomenon in the socio-economic dynamics of the ASEAN region, particularly in countries with negative net migration. This study aims to analyze the influence of socio-economic factors on out-migration rates in five ASEAN countries—Indonesia, Cambodia, Laos, Myanmar, and the Philippines—using a quantitative approach through panel data regression analysis. The independent variables used include wage levels, unemployment rates, labor force size, and the Human Development Index (HDI), with secondary data from 2000 to 2023. The model testing results indicate that the Fixed Effect Model (FEM) is the best model. The findings reveal that wages (coefficient = 0.041; p = 0.0019), unemployment (coefficient = 0.151; p = 0.0025), and HDI (coefficient = 19.91; p = 0.0000) have a significant positive effect on out-migration, while the labor force variable has a significant negative effect (coefficient = -3.456; p = 0.0000). This model explains 97.37% of the variation in emigration rates (R² = 0.9737), with a simultaneous model significance of 0.0000. The conclusion of this study is that migration decisions are not only driven by economic desperation but also by increased individual capabilities that enable cross-border mobility. The implications of this study suggest the need for policies that not only address the drivers of migration but also strengthen the domestic labor market and invest in human development, so that migration can become a safe and productive choice rather than a necessity.